Shadow Economies All over the World : New Estimates for 162 Countries from 1999 to 2007 - Schneider, Friedrich; Buehn, Andreas; Montenegro, Claudio E. (2012)
This paper presents estimations of the shadow economies for 162 countries, including developing, Eastern European, Central Asian, and high-income countries over the period 1999 to 2006/2007. According to the estimations, the weighted average size of the shadow economy (as a percentage of "official" gross domestic product) in Sub-Saharan Africa is 38.4 percent; in Europe and Central Asia (mostly transition countries), it is 36.5 percent, and in high-income OECD countries, it is 13.5 percent. The authors find a clear negative trend in the size of the shadow economy: The unweighted average of the 162 countries in 1999 was 34.0 percent and in 2007 31.0 percent; hence a reduction of 3 percentage points!.The driving forces of the shadow economy are an increased burden of taxation (both direct and indirect), combined with labor market regulations and the quality of public goods and services, as well as the state of the "official" economy.